Exploring recent increases in the gender wealth gap among Australia's single households. (March 2015) - Austen, Siobhan; Ong, Rachel; Bawa, Sherry; Jefferson, Therese
This study uses three wealth modules from the Household, Income and Labour Dynamics in Australia Survey to explore the gender wealth gap for single Australian households between 2002 and 2010. The findings indicate a significant gender wealth gap, which has increased over the 8 years explored. Most of the increase in the wealth gap was associated with a relatively rapid increase in the value of housing assets by single men over the study period. The findings of this study challenge a wider literature that tends to emphasise that men are more prepared to invest in 'risky' assets such as shares and that their higher wealth is due to these investment strategies. Instead, this study emphasises how, in the Australian context at least, it was higher growth rates in the value of housing assets owned by single men that improved their wealth position relative to single women over the last decade.